Pollution Liability: Rediscovery of Policy Language - Glad, Paul E.B.; Forsyth, Thomas L. (Assurances)

(untitled) (HEC Montréal, 1988)
Liability insurers have struggled for years to distinguish pollution incidents which they intend to cover from those they intend to exclude to the satisfaction of the courts. However, as the authors point out here, a number of recent cases indicate the courts' willingness to recognize the intent of policy language. In this exhaustive study, they examine how these cases have shed new light on the rule of ambiguity in policy language, on coverage for cleanup costs, on defense limitations, and on the pollution exclusion itself.